2006
DOI: 10.1123/jtpe.25.1.99
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Dimensions of Urban Teacher Change

Abstract: This study used an emotional geographies theoretical framework to analyze the emotional dimensions of urban teacher change. Fifteen urban physical education teachers involved in a comprehensive curriculum reform project were interviewed and observed multiple times across one school year. Data were analyzed using inductive analysis, and trustworthiness measures included triangulation, peer debriefing, researcher journals, and member checks. Teachers reported that emotional dimensions related to their urban stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 36 publications
1
27
0
5
Order By: Relevance
“…En dichas investigaciones se ha encontrado que las emociones de los profesores se entrelazan con los procesos de transformación y que ellas influyen en su compromiso con el proyecto de cambio, además que, por el estrés que generan las modificaciones, el profesor pierde la felicidad de comunicarse con los estudiantes (McCaughtry, Martin, Cothran y Hodges-Kulinna, 2006;Yin y Lee, 2006). Así pues, Hargreaves dice que la microgestión de estándares basados en las reformas tiene "efectos nocivos en la enseñanza de los profesores, en los estudiantes de los profesores y en las relaciones de los profesores con su trabajo y con los otros" (2003, p. 90).…”
Section: Geografía Emocional De La Enseñanzaunclassified
“…En dichas investigaciones se ha encontrado que las emociones de los profesores se entrelazan con los procesos de transformación y que ellas influyen en su compromiso con el proyecto de cambio, además que, por el estrés que generan las modificaciones, el profesor pierde la felicidad de comunicarse con los estudiantes (McCaughtry, Martin, Cothran y Hodges-Kulinna, 2006;Yin y Lee, 2006). Así pues, Hargreaves dice que la microgestión de estándares basados en las reformas tiene "efectos nocivos en la enseñanza de los profesores, en los estudiantes de los profesores y en las relaciones de los profesores con su trabajo y con los otros" (2003, p. 90).…”
Section: Geografía Emocional De La Enseñanzaunclassified
“…She uses one, two, three, or whatever for them to get quiet and I started using it and she told me some little saying to use and it worked." At least part of the desire for more direct styles seemed related to the difficult context in which the teachers worked (described in McCaughtry, Barnard, Martin, Shen, & Hodges Kulinna, 2006;McCaughtry, Martin, Hodges Kulinna, & Cothran, 2006). Promoting student attendance, engagement, achievement, and proper behavior were major challenges that even experienced teachers struggled with on a daily basis.…”
Section: Direct Mentor Stylesmentioning
confidence: 99%
“…In the other two studies conducted by Solmon, Worthy and Carter (1993), Tsangaridou and O'Sullivan (1997), the experience from three initial teachers and four experienced teachers respectively showed that teachers' role identity and teachers' reflection have a positive relationship on the PE teacher development. More recently, two other issues, such as, teachers' teaching experience and teachers' emotion dimension, were identified to impact the professional development according to the two studies conducted by Ha, Wong, Sum and Chan (2008) and (McCaughtry, Martin, Kulinna and Cothran (2006) respectively.…”
Section: In-service Teachersmentioning
confidence: 99%
“…What are the criteria for the selection of particular collaborative learning strategies? (1) Europe (16) UK (10), Ireland (2), Turkey (1), Spain (1), France (1), Norway (1) Australasia (1) Australia (1) Asia ( Rovegno and Bandhauer (1997a) Perception of teacher role Solmon, Worthy and Carter (1993) Teachers' working experience Ha, Wong, Sum and Chan (2008) Teacher reflection Tsangaridou and O'Sullivan (1997) Teachers' emotional dimensions related to their students, colleagues and statues McCaughtry, Martin, Kulinna and Cothran (2006) Contextual factors…”
Section: Conclusion and Recommendationmentioning
confidence: 99%